2017
DOI: 10.1080/21681805.2017.1411392
|View full text |Cite
|
Sign up to set email alerts
|

Eighteen-year follow-up of the Göteborg Randomized Population-based Prostate Cancer Screening Trial: effect of sociodemographic variables on participation, prostate cancer incidence and mortality

Abstract: These data corroborate previous findings that systematic PSA screening reduces PC mortality and suggest that systematic screening may reduce sociodemographic inequality in PC mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
65
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 24 publications
1
65
1
Order By: Relevance
“…27 Furthermore, data from the 18-year follow up of the G€ oteborg randomized population-based PCa screening trial showed that in standard care, when organized screening did not exist, less-educated men had higher PCa-mortality than more educated men. 28 In contrast, when screening was implemented in an organized way, PCa-mortality was not associated with education, suggesting that organized screening might diminish PCa-mortality differences across patients with various socioeconomic status. 28 Interestingly, health insurance coverage was not significantly associated with PSA testing, despite the notion of perceived barriers with cancer screening in patients who lack health insurance.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…27 Furthermore, data from the 18-year follow up of the G€ oteborg randomized population-based PCa screening trial showed that in standard care, when organized screening did not exist, less-educated men had higher PCa-mortality than more educated men. 28 In contrast, when screening was implemented in an organized way, PCa-mortality was not associated with education, suggesting that organized screening might diminish PCa-mortality differences across patients with various socioeconomic status. 28 Interestingly, health insurance coverage was not significantly associated with PSA testing, despite the notion of perceived barriers with cancer screening in patients who lack health insurance.…”
Section: Discussionmentioning
confidence: 98%
“…28 In contrast, when screening was implemented in an organized way, PCa-mortality was not associated with education, suggesting that organized screening might diminish PCa-mortality differences across patients with various socioeconomic status. 28 Interestingly, health insurance coverage was not significantly associated with PSA testing, despite the notion of perceived barriers with cancer screening in patients who lack health insurance.…”
Section: Discussionmentioning
confidence: 98%
“…Notice that a PSA cut-off value of 2.5 ng/mL has been recently recommended by the National Comprehensive Cancer Network 8 in the United States and the Goteborg trial. 9 This value must be compared with the PSA cut-off value (2.1 ng/mL) we obtained for a small tumor volume. A strong correlation between preoperative total PSA and tumor volume (V T ) was found by Carvalhal et-al.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the 18-year follow-up study from the Goteborg randomized control trial, one center of the ERSPC trial, showed a large and statistically significant relative prostate cancer mortality reduction (RR = 0.31) for the attendees in this age group. 8 Similarly, two other recent studies indicated a possible benefit of screening for this age group. 12,13 Although the overall result reported from the CAP (Cluster Randomized Trial of PSA Testing for Prostate Cancer) trial was insignificant, the highest prostate cancer mortality reduction was seen in this age group.…”
mentioning
confidence: 87%